A clinical data repository enhances hospital infection control. - Samore, M. (American Medical Informatics Association, 1997)
We describe the benefits of a relational database of hospital clinical data (Clinical Data Repository; CDR) for an infection control program. The CDR consists of > 40 Sybase tables, and is directly accessible for ad hoc queries by members of the infection control unit who have been granted privileges for access by the Information Systems Department. The data elements and functional requirements most useful for surveillance of nosocomial infections, antibiotic use, and resistant organisms are characterized. Specific applications of the CDR are presented, including the use of automated definitions of nosocomial infection, graphical monitoring of resistant organisms with quality control limits, and prospective detection of inappropriate antibiotic use. Hospital surveillance and quality improvement activities are significantly benefited by the availability of a querable set of tables containing diverse clinical data.